2017
DOI: 10.1111/acer.13373
|View full text |Cite
|
Sign up to set email alerts
|

Validating Harmful Alcohol Use as a Phenotype for Genetic Discovery Using Phosphatidylethanol and a Polymorphism in ADH1B

Abstract: Background Although alcohol risk is heritable, few genetic risk variants have been identified. Longitudinal (EHR) data offer a largely untapped source of phenotypic information for genetic studies, but EHR-derived phenotypes for harmful alcohol exposure have yet to be validated. Using a variant of known effect, we used electronic health record (EHR) data to develop and validate a phenotype for harmful alcohol exposure that can be used to identify unknown genetic variants in large samples. Herein, we consider t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 21 publications
6
27
0
Order By: Relevance
“…The AUDIT-C yielded many GWS findings that did not overlap with those for AUD, which reflects genetic independence of the traits. This broadens our previous observations using SNPs in ADH1B , in which we validated the AUDIT-C score as an alcohol-related phenotype 33 . In that study, after accounting for the effects of AUDIT-C score, AUD diagnoses accounted for unique variance in the frequency of the minor alleles.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The AUDIT-C yielded many GWS findings that did not overlap with those for AUD, which reflects genetic independence of the traits. This broadens our previous observations using SNPs in ADH1B , in which we validated the AUDIT-C score as an alcohol-related phenotype 33 . In that study, after accounting for the effects of AUDIT-C score, AUD diagnoses accounted for unique variance in the frequency of the minor alleles.…”
Section: Discussionsupporting
confidence: 75%
“…Our analyses used AUDIT-C data collected from October 1, 2007–February 23, 2017. We validated the phenotype in a sample of 1,851 participants from the Veterans Aging Cohort Study 33 , in which we found a highly significant association of AUDIT-C scores with the plasma concentration of phosphatidylethanol, a direct, quantitative biomarker that is correlated with the level of alcohol consumption. In the AA part of this sample (n=1,503), the AUDIT-C score was highly significantly associated with rs2066702, a missense (Arg369Cys) polymorphism of ADH1B , the minor allele of which is common in that population and has been associated with alcohol dependence 25 .…”
Section: Methodsmentioning
confidence: 99%
“…As we found in prior analyses of repeated longitudinal self‐reported measures of alcohol consumption (Justice et al . ; Justice et al . ), summary measures of repeated self‐reported smoking also demonstrate stronger associations than single, cross‐sectional reports that are often employed as phenotypes in large‐scale genetic studies (Sanchez‐Roige et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, PEth was only measured in Cohort 1 using dried blood spot samples derived from frozen peripheral blood mononuclear cells stored at -80°C 5 . PEth can be detected at concentrations as low as 2 ng/ml.…”
Section: Phosphatidylethanol (Peth) Measurementmentioning
confidence: 99%
“…Phosphatidylethanol (PEth) is a lipid metabolite of ethanol formed from phosphatidylcholine in erythrocytes and has been proposed as a biomarker for alcohol consumption. Compared with self-reported data, PEth reliably detects ethanol levels up to 21 days after the last drink 4 , and the PEth level is highly correlated with alcohol consumption 5 . However, the clinical applicability of PEth is limited because its half-life the HAD predicting procedure using the preselected CpGs from the EWAS on AUDIT-C score was also performed.…”
Section: Introductionmentioning
confidence: 97%